Synthesis and characterization of Sn1-xGex anode materials via melt spinning - Goh, Brenda Kheng Leng. (2012)
Due to the increased demands of space efficiency and energy requirements in many applications which utilize Li-ion secondary batteries, there is a search for compounds with high Li storage characteristics which maintain their capacity over extended cycles of charging and discharging. Sn1-xGex anodes display one of the best values for capacity retention over many cycles. Traditionally, these anodes were prepared by physical mixing but we have chosen melt spinning instead due to its high throughput and thus industrial scalability and to study its effects on anodic properties. In this study, various ratios of Sn1-xGex anodes were prepared using the melt spinning process and their cyclic capacity was characterized. The melt spun anodes showed a starting capacity (mAhg-1) of 1300 mAhg-1 compared to physically mixed anodes with 1500 mAhg-1. However, upon cycling, the melt spun anodes showed a stable capacity at 1050 mAhg-1 while the physically mixed anodes dropped steadily to 600 mAhg-1 by cycle 50. Lastly, the Sn2Ge8 ratio was found to have the highest capacity and cycle stability of 1050 mAhg-1 and the lowest to be Sn8Ge2.